Non-haemorrhagic, bilateral adrenal infarction in a patient with antiphospholipid syndrome along with lupus myocarditis. (20th July 2016) - Batt, Nicholas Marinus; Malik, Dean; Harvie, Miranda; Sheth, Hemant
Abstract : A 40-year-old woman with antiphospholipid syndrome presented with a 5-day history of right upper quadrant (RUQ) pain, radiating posteriorly, associated with fever and vomiting. She was admitted 1-week prior with an upper respiratory infection and erythema multiforme. Clinical assessment revealed sepsis with RUQ tenderness and positive Murphy's sign. Laboratory results showed raised inflammatory markers, along with renal and liver impairment. CT showed bilateral adrenal infarction and inferior vena cava thrombus. The patient was managed for sepsis and started on heparin. Further immunological investigations revealed a diagnosis of systemic lupus erythematous, an exacerbation of which culminated in lupus myocarditis. This case illustrates the importance of promptly recognising adrenal insufficiency in patients with antiphospholipid syndrome and the possible causative agents, which require careful consideration and exclusion to prevent further thrombotic events. It also highlights the importance of undertaking imaging, namely CT, in patients with antiphospholipid syndrome presenting with abdominal pain as well as considering concomitant autoimmune conditions.